Food chains; the cradle for scientific ideas and the target for technological innovations. (April 2018) - Abecassis, Joel; Cuq, Bernard; Escudier, Jean-Louis; Garric, Gilles; Kondjoyan, Alain; Planchot, Véronique; Salmon, Jean-Michel; de Vries, Hugo
Abstract: Research in the area of emerging food science and technology is still often carried out in agri-food chain perspectives, as presented here in four different ways for dairy, meat, wine and cereal cases. The key focus is on the concept of food quality throughout the chain, and the meaning of added value and food functionalities for consumers. Technology innovation approaches essentially address ways to optimize and maintain food quality according to consumer preferences, needs and acceptances. However, they also strive to reduce the environmental impact of the transformation of agroresources into food products, via targeted and intensified processing schemes requiring minimal energy and water usage, as well as value-streaming co-products of used agroresources—which holds for all the chains presented. Another key area that emerges from the cases is protein science, which concerns agroresources rich in specific protein and, protein heterogeneity, structural changes, profiles, functionalities and nutritional value. This analysis further highlights the importance of linking food science and technology to agronomy, genetics, and socioeconomic sciences. Finally, knowledge management is becoming increasingly integral to food chain research in order to increase transparency and capitalize data in a consistent manner. Highlights: Food chain research is still the cradle of many new research and innovation topics A cross-cutting view on chains reveals topics as plant protein science, ecodesign approaches, and food-system thinking Environmental pressure on food systems links scientists all along the food chain Food science is becoming an increasingly inter-disciplinary and inter-sector cooperation effort